Corporate governance and performance of private domestic banks in Sri Lanka: Current status and areas for reforms - Wickramasinghe, A.A.I.N (My University, 2018)
The stability of the banking sector is of utmost importance for the economic and financial development of a country. However, the stability of the banking sector become an issue due to sudden failures of banking institutions. With that, corporate governance has been identified as a mechanism which can be used to prevent such failures since it has the ability to improve the governance structure and thereby the soundness and healthiness of banks. Therefore, corporate governance has been introduced and promoted among banks all over the world during the last few decades. Accordingly, this study investigates the impact of introducing corporate governance principles on PDBs of Sri Lanka during the period from 2004 to 2015. This study focuses on four objectives, and mixed methods of research are employed to achieve these objectives. In relation to the first and second objectives, quantitative research method is employed. i.e. 1). to examine the level of compliance on corporate governance by PDBs of Sri Lanka; and 2). to investigate the impact of individual corporate governance mechanisms and the level of compliance on the performance of PDBs of Sri Lanka. CGCI was constructed by the researcher to measure the level of compliance. Panel data regression analysis was employed to examine the impact of corporate governance on the performance of PDBs of Sri Lanka and data was collected from the annual reports of the individual banks. ...